Alternating current properties of bulk- and nanosheet-graphitic carbon nitride compacts at elevated temperatures - Tosapol Maluangnont; Phieraya Pulphol; Kanokwan Chaithaweep; Klichchupong Dabsamut; Thawanrat Kobkeatthawin; Siwaporn Meejoo Smith; Adisak Boonchun; Naratip Vittayakorn (RSC Advances, 2023)
(∼0.09) compared to the bulk counterpart, demonstrating its potential as a highly insulating, stable dielectrics at elevated temperatures.
Keywords: Ga2O3 and related materials; ZnO doping and properties; Graphene research and applications